Environmental Impact Assessment of Biofuel Production: A Life Cycle Analysis of Key Indicators and Mitigation Strategies - Usanova Kseniia Iurevna; Siri Dharmapuri; Rao Peram Kondala; Chhetri Abhishek; Sudan Prerak; Sharma Prabhat; Kumar Raman (E3S Web of Conferences)
This research analyzes the environmental impacts of biofuel production through a life cycle assessment (LCA), focusing particularly on ten fundamental elements. Studies indicate that the production of biofuels has had a notable effect on several aspects: the possibility of depletion of non-renewable resources (22.34 kg eq Sb), the capacity for acidification (14.23 kg eq SO₂), the likelihood of eutrophication (4.1 kg eq PO₄³⁻), and the impact on global warming (2400 kg eq CO₂). Notable progress has been made in the treatment of fuels, the cultivation of natural resources, and the use of diesel. The danger that can affect humanity is quite considerable, reaching a total of 3100.5 kilograms of 1,4- difluorobenzene equivalent, primarily resulting from the significant impact of fuel conversion, which amounts to 1400 kilograms. Five hundred kilograms. The influence of ocean environmental toxicity is significant, reaching 210,000 kilograms of 1,4-difluorobenzene equivalent, mostly originating from fuel manufacturing and the agriculture of raw materials. Although biofuels have a lower environmental impact than fossil fuels in terms of global warming, they still face challenges such as acidification, eutrophication, and toxicity. It is proposed to employ environmentally friendly agricultural techniques, implement precision agriculture, and incorporate renewable energies to mitigate these impacts and enhance the ecological advantages of biofuel production.